Interaction of Surface Plasmons with CdTe quantum dot excitons - Lunney, James; Donegan, John; Bradley, Louise; Donnelly, Tony; Vamsi, Komarala; Rakovich, Yury; Doggett, B.; Gaponik, Nikolai; Susha, A. (My University, 2005)
A 5-fold enhancement in the luminescence of CdTe nanocrystal quantum dots (QDs) is observed when they are placed in proximity to a nanostructured Au film deposited by pulsed laser deposition technique. No enhancement is observed with a nanostructured Ag film. The enhancement is due to the interaction of the QDs excitons with the localized surface plasmons (LSP). The Au surface plasmon (SP) frequency is closer to the QDs emission frequency than Ag LSP frequency and this accounts for the differences in observed behavior. As the SP-QD interaction strongly depends on the geometric structure and shape of the metal nanoparticles, a comparison with QDs deposited on a film of Au colloidal nanoparticles is presented. In the case of QDs placed directly on the Au colloids the luminescence quenching is much stronger and with a spacer layer a 3.5-fold enhancement over the bare QDs luminescence is observed.
PUBLISHED
Keywords: Semiconductor quantum dots; Luminescence; CdTe